Innovation, Knowledge Sharing and Islamic Leadership Model in the Islamic School - Nasution, Ali Hanafiah; Muliati, Lisdewi; Hasan, Muh (International Journal of Social and Management Studies, 2022)
This study investigates the impact of self-leaderships within teachers in the Islamic schools in Indonesia towards teacher innovation and evaluates the impact of mediation from knowledge sharing to this relationship. 95 teachers in the Islamic schools participate in this research. The result of research claimed that self-leadership has a positive and significant effect on knowledge sharing and teacher innovation. Likewise, knowledge sharing has a positive and significant effect on teacher innovation. Therefore, the result of the research showed that knowledge sharing has a partial mediation impact on the relationship between self-leadership and teacher innovation.